Tax on wages as a mechanism for self-correction to ease economic fluctuations Algeria's case study for the period 1992-2015 using a mile Hodrick- Prescott (HP). - جبارة, مراد; يجياوي, الياس (Université de M'sila, 2017)
Taxes are considered generaly on income and particulary on wages one of the most important self-stability tools ,as a progressive taxes , We have tried in this research know how important this tool in mitigating economic fluctuations in Algeria without any active policy , We have found that taxes on wages constitute a large proportion of the total income taxes reached the lowest to 68%to excel the 90 per cent in some cases,but although this considerable position we have found that despite the tax system changes there was a slight modification in income taxes ((Wages in particular) as an automatic stabilizing factor .But after a 2008 reform, income tax appears to be assuming its role as an automatic stabilizer.
Keywords: taxes on wages, automatic stability, fiscal flexibility, economic stability.